Anisotropic oxide ion conduction in melilite intermediate temperature electrolytes - Wei, Fengxia (2016)
Electrolytes with oxide ion conductivities higher than 10−2 S cm−1 at moderate temperatures (∼500–900 °C) offer the possibility for solid oxide fuel cells to operate with less maintenance. This study of [A1+xB1−x]2[Ga]2[Ga2O7+x/2]2 (0 ≤ x ≤ 0.5) (A = La, Nd; B = Ca, Sr) layered-melilite found that in large single crystals intralayer oxide ion conduction is dominant. This anisotropic behavior arises by relaxation about the interstitial oxygen through changes in the interlayer A and Ga coordination, and at 850 °C conductivities are ∼0.008 S cm−1 along the c direction and ∼0.036 S cm−1 perpendicular to the c axis. It is found that the ionic conductivity can be optimized by increasing the number of interstitial oxygen and reducing the size of interlayer cations.